Methods of wintering yearling steers on dry bluestem pasture. - Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
This test is to determine if yearling steers can be wintered satisfactorily on dry bluestem pasture. Different protein supplements as well as methods of feeding them on dry bluestem pasture are being tested. Forty head of good quality Hereford yearling steers, four lots, 10 head to a lot, were used in this test. All lots were wintered on dry bluestem pasture. Each lot had sufficient dry grass to winter on; the acreage varied from 6 acres per head for one lot to 19 acres per head for another lot. All pastures had been normal stocked the previous grazing season.
Keywords: Beef; Steers; Dry bluestem pasture; Protein